1991
DOI: 10.1104/pp.96.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Expression and Anaerobically Induced Posttranscriptional Modulation of Sucrose Synthase Genes in Sorghum bicolor M.

Abstract: We have used antibodies directed against the two sucrose synthase (SS) isozymes, and the cDNA clones corresponding to the two nonallelic genes in maize to describe sorghum (Sorghum bicolor) SS genes and their expressions at protein and RNA levels. Westem blot analyses have shown evidence of two SS isozymes, SS1 and SS2, in sorghum; these were similar, but not identical, to maize isozymes in size, charge, subunit composition, and epitope specificities against both monoclonal and polyclonal antibodies. Tissue-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…In maize, three Sus genes have been identified . Five Sus isoforms have been detected in Sorghum bicolor (Chourey et al, 1991). Silvente et al (2003) indicated that there are at least two Sus genes in common beans (P. vulgaris).…”
Section: Sucrose Synthase (Sus)mentioning
confidence: 99%
“…In maize, three Sus genes have been identified . Five Sus isoforms have been detected in Sorghum bicolor (Chourey et al, 1991). Silvente et al (2003) indicated that there are at least two Sus genes in common beans (P. vulgaris).…”
Section: Sucrose Synthase (Sus)mentioning
confidence: 99%
“…The filter was probed with a 32 P-labeled potato sucrose synthase cDNA clone (Salanoubat and Belliard, 1987 Wang et al, 1993b) and was similar to that of the potato sucrose synthase transcript from tubers (Salanoubat and Belliard, 1987). Analysis of sucrose synthase copy number in maize (Echt and Chourey, 1985) and sorghum (Chourey et al, 1991b) indicates that there are two genes per haploid genome. Southern blot analysis of tomato genomic DNA hybridized under identical conditions as the northern blots indicated that the probe used in these studies hybridized to only one RNA species (data not shown).…”
Section: Sucrose Synthase Gene Expression In Tomatomentioning
confidence: 99%
“…Its main physiological importance is to cleave SUC, providing UDP-Glc for starch, cellulose, hemicellulose synthesis, and respiration (Huber and Akazawa 1986;Sung et al, 1988;Chourey et al, 1991b).…”
mentioning
confidence: 99%
“…Excised embryos were homogenized using 1.0 g of fresh weight to 5.0 ml of grinding buffer (0.01 M Tris-maleate, pH 7.0), strained through glass wool, and centrifuged at 20,000 x g for 20 min (21). Samples were electrophoresed on a 4.5-7.0% linear gradient nondenaturing polyacrylamide gel, electroblotted to nitrocellulose, and immunostained using the appropriate primary antibody as detailed previously (16,21,22). DNA Analyses.…”
mentioning
confidence: 99%